(untitled) (European Journal of Education and Psychology, 2010)
One of the most important keys to preventing or treating school coexistence problems is to know effective instruments, techniques and procedures. The aims of this paper are to analyze if pre-service teachers know some of the most important resources to keep a good school climate and, secondly, if they are satisfied with the training that they are receiving at university about these resources. One hundred and twenty six students of the last course of Teacher Training degree at Oviedo University were assessed with an “ad hoc” questionnaire. The results show a poor knowledge of many of the assessed resources and a low satisfaction with received training.